Regular Consumption of Cocoa and Red Berries as a Strategy to Improve Cardiovascular Biomarkers via Modulation of Microbiota Metabolism in Healthy Aging Adults - García-Cordero, Joaquín; Martinez, Alba; Blanco-Valverde, Carlos; Pino, Alicia; Puertas-Martín, Verónica; San Román, Ricardo; de Pascual-Teresa, Sonia (Nutrients, 2023)
The aim of the present study was to analyze the effects of cocoa flavanols and red berry anthocyanins on cardiovascular biomarkers, such as homocysteine, angiotensin-converting enzyme (ACE), nitric oxide (NO), flow-mediated vasodilation (FMD), blood pressure and lipid profile. Additionally, we aimed to ascertain their possible interactions with microbiota related metabolites, such as secondary bile acids (SBA), short-chain fatty acids (SCFA) and trimethylamine N-oxide (TMAO). A randomized, parallel-group study, single-blind for the research team, was performed on 60 healthy volunteers between the ages of 45 and 85, who consumed 2.5 g/day of cocoa powder (9.59 mg/day of total flavanols), 5 g/day of a red berry mixture (13.9 mg/day of total anthocyanins) or 7.5 g/day of a combination of both for 12 weeks. The group that had consumed cocoa showed a significant reduction in TMAO (p = 0.03) and uric acid (p = 0.01) levels in serum, accompanied by an increase in FMD values (p = 0.03) and total polyphenols. corrected by creatinine (p = 0.03) after the intervention. These latter values negatively correlated with the TMAO concentration (R = −0.57, p = 0.02). Additionally, we observed an increase in carbohydrate fermentation in the groups that had consumed cocoa (p = 0.04) and red berries (p = 0.04) between the beginning and the end of the intervention. This increase in carbohydrate fermentation was correlated with lower levels of TC/HDL ratio (p = 0.01), systolic (p = 0.01) and diastolic blood pressure (p = 0.01). In conclusion, our study showed a positive modulation of microbiota metabolism after a regular intake of cocoa flavanols and red berry anthocyanins that led to an improvement in cardiovascular function, especially in the group that consumed cocoa.
Keywords: anthocyanins; bile acids; cardiovascular; flavanols; short-chain fatty acids; TMAO; Scopus; JCR